Tanzania 2019 Country Environmental Analysis : Environmental Trends and Threats, and Pathways to Improved Sustainability - World Bank Group (World Bank, Washington, DC, 2019)
Tanzania’s wealth per capita has declined because its rapid population growth has outpaced investment. This decline in wealth is almost entirely accounted for by its “renewable natural capital” loss, consisting of the country’s agricultural land, cropland, forests, forest products, and protected areas. The country’s human capital per capita is stable while its physical capital per capita has risen by 13 percent. Yet its degrading natural capital base clearly illustrates the magnitude of its sustainability problem: the total renewable natural capital per capita has fallen by 35 percent over the past 20 years, whereas the non-land renewable natural capital per capita has declined by 47 percent (that is, almost halved in 20 years). Tanzania cannot afford another 10 years of the same negative trends in resource degradation. The opportunity Tanzania faces is to reconcile the use of natural resources to meet the demands of the population and economy with the need to maintain functioning ecosystems. Reaching this balance will catalyze sustained growth. However, the current trend in the use of natural resources is not sustainable, leading to persistent degradation and loss of ecosystems, which constitute the main cause of the natural capital. This CEA has identified spatially and temporally differentiated approaches and solutions toward ensuring sustainable resource management for long-term use.